Stimulating Literacy Skills in 5-6 Year Old Children Using the Make A Match Model Assisted by Flash Cards - Ananda, Erdianty Putri; Winda Sherly Utami; Akhmad Fikri Rosyadi (JURNAL PENA PAUD, 2025)
Literacy skills are a crucial foundation for early childhood, determining their readiness to enter further education. This study aims to evaluate the effectiveness of the Make A Match learning model, when supplemented with flashcards, in enhancing the literacy skills of children in Group B (aged 5-6 years) at Harokatil Islamiah Kindergarten. The method employed was a pre-experimental study with a One-Group Pretest-Posttest Design, involving 12 children as the sample. Data were collected through performance tests and analyzed using a paired-samples t-test. The results showed a significant increase. The average literacy score of the children increased from 12.16 (43.45% of the ideal score) on the pretest to 20.08 (71.72%) on the posttest. Further analysis revealed that this difference was statistically significant (p-value = 0.000, p < 0.05). These findings confirm that the Make A Match model, using flashcards, not only provides a fun and interactive learning experience but also positively affects the development of children's early literacy skills. This card-matching activity successfully trains phonological awareness, letter recognition, and other cognitive skills in a way that children enjoy. This study recommends this model as an innovative learning strategy alternative that educators and parents can adopt